Common Law Director Duties and Shareholder Remedies as codified into the UK Companies Act 2006 - Ngcetane-Vika, Thelela (My University, 2023)
The UK Companies Act 2006 is a pioneering statutory instrument, hailed for its success in the codification of common law rules and simultaneously influencing reforms and harmonising the company rules, allowing for easy application and certainty. The general rule is that the twin set of shareholder and directors, through the doctrine of separation of ownership and control, play a critical role in running a company's affairs. Further, the reforms also brought judicial clarity for courts to interpret and apply the law with relative ease and legal certainty. These reforms became the cornerstone of corporate governance, with several commonwealth jurisdictions like South Africa’s 2008 Companies Act borrowing heavily from the UK. Correspondingly, the UK Companies Act has been pivotal in setting the scene for South African Companies Act. This study aims to conduct a qualitative research on the codification of the director’s duties in the UK Companies Act 2006, using legal theory. Thus, the empirical basis for this examination includes secondary sources, including a literature review of books, articles, case law and relevant Statutes. Both content and thematic analysis were employed. It is anticipated that the recommendations of this study could assist policy-makers, leaders and contribute to the body of legal knowledge.
Keywords: Codification; Common law; Companies Act; Director’s duties; Shareholder Remedies